Speciation of Uranium and Plutonium From Nuclear Legacy Sites to the Environment: A Mini Review - Romanchuk, Anna Yu.; Vlasova, Irina E.; Kalmykov, Stepan N. (Frontiers in Chemistry, 2020)
The row of 15 chemical elements from Ac to Lr with atomic numbers from 89 to 103 are known as the actinides, which are all radioactive. Among them, uranium and plutonium are the most important, as they are used in the nuclear fuel cycle and nuclear weapon production. Since the beginnings of national nuclear programs and nuclear tests, many nuclear legacy sites, namely, radioactively contaminated areas, have been formed. This mini review covers the latest experimental, modeling and case study achievements in the investigation of plutonium and uranium migration in the environment, which include the speciation of these elements and the chemical reactions that control their migration pathways.